MODIFIKASI PROSES PEMBUATAN KARET ALAM SIKLIS (CYCLIC NATURAL RUBBER) MELALUI REAKSI PEMUTUSAN RANTAI (CHAIN SCISSION) DAN SIKLISASI - Eddyanto ,; Yuslina Wati Ardina; M. Said Siregar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
Cyclization of natural rubber has been carried out by the chain scission process preceded earlier. Chain scission process performed in a solution of phenol at a temperature of 1800C by using Brosse method, oxidation reaction with fenilhidrazin and oxygen . While the cyclization of natural rubber was conducted by Tutorskii method , using lewis acid catalyst, P2O5. Characterization of raw materials and products of the chain scission and cyclization performed by infrared spectroscopy analysis. The infra red spectra showed the strong peak at 2925 cm-1 and 1446 cm-1 , reduced absorption at 1600s cm-1, the emergence of a new peak at 757 cm-1 and a weaker absorption peak at 835 cm-1. The absorption peaks of cyclic natural rubber of crumb rubber ( SIR - 10 ) also changed . The results showed that the percentage of chain scission were 13.1 % on the latex and 2 % on the SIR - 10 . While the percentage of cyclization yield of latex and SIR - 10 were 22.8 and 73.1 %, respectively.Keywords : cyclic natural rubber, chain scission, cyclization